BURUH TANI DALAM HUKUM POSITIF INDONESIA:: Sebuah Kajian Perundangan untuk Upaya Gagasan Perlindungan - A'isyah, Siti (Malang Prodi. Ahwal Al-Syakhsiyyah, IAI Al-Qolam, 2022)
Farm labor or peasant is an urgent component in agriculture, farm and animal husbandry or aquaculture. Farm workers or peasants also have unique and different characteristics compared to industrial workers, especially in terms of form and rhythm of work. However, farm workers do not get specific protection in positive law in Indonesia. This article explores the legislation in Indonesia to see the position of farm workers in positive law. The search results, supported by the elaboration of historical facts, show that agricultural laborers in Indonesia do not have a specific legal protection. Meanwhile, the facts of current agricultural developments show that farm workers increasingly need this protection in line with the tendency of agricultural globalization.